A Longitudinal Study of the Epidemiology of Seasonal Coronaviruses in an African Birth Cohort. (2nd February 2021) - Nicol, Mark P; MacGinty, Rae; Workman, Lesley; Stadler, Jacob A M; Myer, Landon; Allen, Veronica; Ah Tow Edries, Lemese; Zar, Heather J
Abstract : A longitudinal study of African infants showed that endemic coronavirus infections were common and weakly associated with lower respiratory tract infection (LRTI), particularly coronavirus-OC43, which was also associated with hospitalized LRTIs. Abstract: Background: Since non-epidemic, seasonal human coronaviruses (sHCoV) commonly infect children, an improved understanding of the epidemiology of these infections may offer insights into the context of severe acute respiratory syndrome (SARS)-CoV-2. We investigated the epidemiology of sHCoV infection during the first year of life, including risk factors and association with lower respiratory tract infection (LRTI). Methods: We conducted a nested case-control study of infants enrolled in a birth cohort near Cape Town, South Africa, from 2012 to 2015. LRTI surveillance was implemented, and nasopharyngeal swabs were collected fortnightly over infancy. Quantitative PCR detected respiratory pathogens, including coronaviruses-229E, -NL63, -OC43, and -HKU1. Swabs were tested from infants at the time of LRTI and from the 90 days prior as well as from age-matched control infants from the cohort over the equivalent period. Results: In total, 885 infants were included, among whom 464 LRTI events occurred. Of the 4751 samples tested for sHCoV, 9% tested positive, with HCoV-NL63 the most common. Seasonal HCoV detection was associated with LRTI; this association was strongest for coronavirus-OC43, which was also found in all sHCoV-associated hospitalizations. Birth in winter was associated with sHCoV-LRTI, but there were no clear seasonal differences in detection. Co-detection of Streptococcus pneumoniae was weakly associated with sHCoV-LRTI (odds ratio: 1.8; 95% confidence interval: 0.9-3.6); detection of other respiratory viruses or bacteria was not associated with sHCoV status. Conclusions: Seasonal HCoV infections were common and associated with LRTI, particularly sHCoV-OC43, which is most closely related to the SARS group of coronaviruses. Interactions of coronaviruses with bacteria in the pathogenesis of LRTI require further study.